2013
DOI: 10.1002/cphc.201300664
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐Engineered Modulation on the Electronic Properties of Phosphorous‐Doped ZnO

Abstract: The modulation of strain on the electronic properties of ZnO:P is investigated by density functional theory calculations. The variation of formation energy (E(f)) and band structure with strains ranging from -0.1 to 0.1 are considered. Although both the conduction band minimum (CBM) and the valence band maximum of ZnO are antibonding states, the CBM is more sensitive to strain, reducing the band gap with an increase in strain. P-substituted O (PO) defects show poor p-type conductivity due to a smaller E(f) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 74 publications
(66 reference statements)
2
15
1
Order By: Relevance
“…61 This immediately implies that the binding energy E b needs to be larger than either of E for (A) and E for (B). As reported previously, wavefunctions of extra free electrons are so dispersed that it could produce a local repulsive stress in the lattice, 63,64 and thus the variation of the electronic environment limits the solubility of the Sn In defect. Therefore, it is evident that the Zn In -Sn In complex should be codoped into the In 2 O 3 supercell easier than the isolated Sn In or Zn In defect during the preparation process of IZTO materials.…”
Section: Zn and Sn Cosubstitutionmentioning
confidence: 75%
See 1 more Smart Citation
“…61 This immediately implies that the binding energy E b needs to be larger than either of E for (A) and E for (B). As reported previously, wavefunctions of extra free electrons are so dispersed that it could produce a local repulsive stress in the lattice, 63,64 and thus the variation of the electronic environment limits the solubility of the Sn In defect. Therefore, it is evident that the Zn In -Sn In complex should be codoped into the In 2 O 3 supercell easier than the isolated Sn In or Zn In defect during the preparation process of IZTO materials.…”
Section: Zn and Sn Cosubstitutionmentioning
confidence: 75%
“…For ITO materials, when the isolated Sn In defect forms, for the reason of Sn 4+ is a tetravalent ion with respect to the In 3+ ion, it would induce an extra free electron. As reported previously, wavefunctions of extra free electrons are so dispersed that it could produce a local repulsive stress in the lattice, 63,64 and thus the variation of the electronic environment limits the solubility of the Sn In defect. The electronic environment effect is also confirmed by the change of lattice parameters during the substitution process.…”
Section: Zn and Sn Cosubstitutionmentioning
confidence: 75%
“…However, the atomic size of an element is not constant as one might expect and is determined by both the intrinsic size (e.g., the covalent radius) and the electronic environment. 27,28 Thus, a dopant induced volume change arises as a result of two factors: the intrinsic size difference DV i and the electronic environment induced volume change DV e . Thus, the charge state of the defect is also a critical parameter used to determine the geometrical structure of a SnO 2 :C supercell.…”
Section: Resultsmentioning
confidence: 99%
“…[38] This indicates the symmetry of the local structure is a critical factor to analyze magnetic moment. [16,42] Therefore, the similarities and differences between these (110), (100) and (101) SnO 2 surfaces are investigated by series of density functional theory (DFT) calculations. Considering the local symmetry variation and Jahn-Teller effect, it is found that magnetism emerges in all of the three surfaces, but the performance and the corresponding mechanism are distinct manifestly between them.…”
Section: Introductionmentioning
confidence: 99%